2011
DOI: 10.1042/cbi20100346
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of CD3zeta is a breast cancer biomarker associated with immune suppression

Abstract: This work was done to establish a correlation between serum protein expression profiles and breast cancer. A high-density antibody microarray was used to identify serum protein expression profiles. Proteins up- or down-regulated by 2-fold compared with normal controls were used for hierarchical clustering analysis. ELISA and immunohistochemistry were used for validation of protein array data. The CD3zeta chain was one of the down-regulated molecules identified by the antibody array analysis and confirmed by EL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…To assess whether melanoma-infiltrating immune cells were functional within MBMs, we stained tumor sections for CD247, the f chain of the TCR that is essential for amplification of TCR signaling and is frequently lost in cancer. 16 Although CD247 1 mononuclear cells were detectable, high numbers of CD247 1 cells were infrequently observed. In addition, neither peritumoral CD4 1 and CD14 1 mononuclear cells nor the presence of any intratumoral mononuclear cell population tested were associated with prolonged OS (Table 4).…”
Section: Validation Of Wgep and Histopathologic Datamentioning
confidence: 99%
“…To assess whether melanoma-infiltrating immune cells were functional within MBMs, we stained tumor sections for CD247, the f chain of the TCR that is essential for amplification of TCR signaling and is frequently lost in cancer. 16 Although CD247 1 mononuclear cells were detectable, high numbers of CD247 1 cells were infrequently observed. In addition, neither peritumoral CD4 1 and CD14 1 mononuclear cells nor the presence of any intratumoral mononuclear cell population tested were associated with prolonged OS (Table 4).…”
Section: Validation Of Wgep and Histopathologic Datamentioning
confidence: 99%
“…Residual cancer cells can be eliminated by effector cells after recognition by the host immune system in breast cancer as well as in other cancers . The underlying mechanism mediated by the suppression of the anti‐tumor immune system has been elucidated, and suppression of the host immune system is known to induce tumor relapse postoperatively . The postoperative relapse involving an immunological mechanism is difficult to eliminate because of the stimulation of residual cancer cells.…”
mentioning
confidence: 99%
“…5,6 The underlying mechanism mediated by the suppression of the anti-tumor immune system has been elucidated, and suppression of the host immune system is known to induce tumor relapse postoperatively. [7][8][9][10] The postoperative relapse involving an immunological mechanism is difficult to eliminate because of the stimulation of residual cancer cells. Among the mechanisms by which tumors evade the anticancer host immune system, ectopic expression of non-classical human leukocyte antigen (HLA) class Ib proteins (HLA-E, HLA-F and HLA-G) on cancer cells has been studied extensively.…”
mentioning
confidence: 99%
“…CD247 encodes the CD3 zeta chain protein; a previous study has shown that the down-regulation of CD3 zeta expression plays an important role in breast cancer progression [ 74 , 75 ];…”
Section: Resultsmentioning
confidence: 99%